Health management practices in chronic traumatic brain injury rehabilitation: A scoping review protocol - Davina Sharma; Shané J. Gill; Lizbeth Goodman; Amanda Rabinowitz; Louis N. Hunter; Reinhard Schaler; Kirby Wycoff (PLoS ONE, 2026)
Introduction Traumatic brain injury is increasingly recognized as a chronic condition requiring long-term rehabilitation and coordinated care beyond the acute phase. Across Europe, substantial variation exists in healthcare system organization, funding structures, and service delivery models, which may influence access to rehabilitation and long-term functional outcomes for adults with chronic moderate-to-severe traumatic brain injury. The objective of this scoping review protocol is to systematically characterize systemic factors and management practices that shape rehabilitation access, continuity of care, and recovery outcomes across European healthcare systems. This review will map published evidence on health management practices influencing chronic traumatic brain injury rehabilitation in Europe and identify gaps for future research. Methods and Analysis This review will follow the Joanna Briggs Institute methodology for scoping reviews. A comprehensive search of PubMed, Scopus, Ovid, and CINAHL will identify studies published between 2018 and 2025 involving adults aged 18 years or older who are at least 1-year post-injury. Studies examining health management practices (i.e., individual, organization, and systemic factors) within European healthcare context will be included. Two reviewers will independently screen articles using predefined inclusion criteria and documented using a Preferred Reporting Items for Systematic Reviews and Meta-Analyses extension for Scoping Reviews flow diagram. Data will be synthesized descriptively through tables, figures, and narrative summaries to map existing evidence and identify gaps in the literature.